Present and Future Conflict Environment: Challenges for Pakistan - Iram Khalid (Journal of Political Studies, 2012)
US occurrence has actively contributed in aggravating the security situation in the region of South Asia. US war on terror has affected Pakistan significantly. This war has posed serious challenges for Pakistan military and political leadership. Worsening economic condition has added a frustrated dimension in this war. There has been a serious lack of comprehension between political leadership and Pakistan military on the perception of threat, nature of conflict and development of consensus on resolving these conflicts and moulding a favourable public opinion. This grim scenario on national and regional level is the consequence of global security environment. In past Pakistan’s security policies was mainly India centric while US served as a prime factor in the backdrop. In present the situation is reversed. Pakistan’s security policies are mainly US centric in post 9/11 era. The present study is an effort to analyse the existing realities.